Assessment Model for Education in Health, based on Games and Virtual Environments. - Thaíse Kelly de Lima Costa; Liliane S Machado; Ana Maria Gondim Valença; Ronei M. Moraes (Universidade de Brasília, 2016)
This paper presents a study of decision models in portals of games and virtual environments, and it shows a new decision model that analyzes the performance of students, considering the cognitive, affective and psychomotor domains. From the research, this study reveals that portals of games and virtual environments for health can include assessment processes, to monitor activities for health education. Understanding that the planning of these activities must be oriented by educational objectives, this work considers these objectives in the assessment process in health and presents a decision model based in the Taxonomy of Educational Objectives. This model can be considered as an alternative to performance assessment based on objective measures of performance in the portals of games and virtual environments.